Chinese–Ukrainian Cooperation Under the Framework of the Belt and Road Initiative - Борділовська, О. А.; Угву, В. У. (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2019)
The current state of development of geopolitical processes marked a tendency towards a bipolarization of the world order. Global economic processes are evidence of China’s aspiration for wider representation in global politics and trade, if not the economic expansion. In this context, the implementation of the One Belt, One Road strategy opens up new opportunities not only for China itself, but also for its strategic partners. In the course of study of the prospects of Chinese-Ukrainian relations, it was established that there are a number of important prospects of Ukraine’s involvement in this geo-economic project. Analysis of the dynamics of foreign trade in goods between Ukraine and China revealed the need to intensify domestic industrial production. As a result of study of the prospects for expanding Ukraine’s participation in the One Belt, One Road project, not only the need to increase export earnings to China, but also identify opportunities for expansion into new markets in eastern direction was established. An important conclusion of the study was that the main emphasis in the further development of Chinese-Ukrainian relations should be directed at active attraction of the Chinese investment in domestic infrastructure projects. Special attention is also paid to the Ukraine’s initiative regarding the expansion of the New Silk Road in the direction of the Danube shipping, which will make it possible to more fully realize the trade and infrastructure potential of Ukraine.

Сучасний стан розвитку геополітичних процесів ознаменував тенденцію до біполяризації Світу. Глобальні економічні процеси свідчать про прагнення Китаю до розширенняприсутності у світовій політиці і торгівлі, є навіть припущення про прагнення КНР до торгівельної та економічної експансії. В цьому контексті реалізація стратегії «Один пояс, один шлях» відкриває нові можливості не лише для самого Китаю, але і для його стратегічних партнерів. Досліджуючи перспективи китайсько-українських відносин, автори встановлюють наявність низки важливих перспектив залучення України у вказаний геоекономічний проект. Аналіз динаміки зовнішньої торгівлі товарами України з Китаєм розкриває необхідність інтенсифікації вітчизняного промислового виробництва. Розглянуто перспективи розширення участі України в проекті «Один пояс, один шлях» встановлено не лише можливість збільшити експортні надходження до Китаю, але і певні можливості для експансії на нові ринки в східному напрямку. Важливим висновком дослідження стало те, що основний акцент в подальшому розвитку китайсько-українських відносин повинен спрямовуватися на активне залучення китайських інвестицій у вітчизняні інфраструктурні проекти. Особлива увага приділяється також ініціативі України щодо розширення Поясу і Шляху в напрямку дунайського судноплавства, що дасть змогу реалізувати торгівельний та інфраструктурний потенціал України в більшій мірі.
Китайсько-українське співробітництво в межах ініціативи «Один пояс – один шлях»
Keywords: Chinese-Ukrainian relations; One Belt; One Road; Silk Road Economic Belt; infrastructure projects; transport corridors; transit of goods; китайсько-українські відносини; «Один пояс; один шлях»; Економічний пояс Шовкового шляху; інфраструктурні проекти; транспортні коридори; транзит товарів